Upaya Penanggulangan Tindak Pidana Pertambangan Ilegal di Wilayah Hukum Kabupaten Tulang Bawang Provinsi Lampung - Refi Meidiantama; Fristia Berdian Tamza; Mamanda Syahputra Ginting (Penerbit Goodwood, 2026)
Purpose: This study examines the efforts to combat illegal mining activities in the jurisdiction of Tulang Bawang Regency, Lampung Province, by analyzing both penal and non-penal approaches as well as the effectiveness of law enforcement through the lens of legal substance, legal structure, and legal culture. Methodology: Using a normative juridical approach, this research relies on primary and secondary legal materials. Primary data were obtained from interviews with key informants and relevant case observations, while secondary data were collected from legislation, books on penal policy, scientific journals, and previous studies related to criminal law enforcement in the mining sector. Results: The findings reveal that the penal approach, as regulated in Law No. 3 of 2020 on Mineral and Coal Mining and the Law on Environmental Protection and Management, provides a strong legal basis to impose criminal sanctions on illegal mining actors. However, law enforcement remains constrained by overlapping regulations, complex licensing procedures, limited resources of law enforcement agencies, and low public legal awareness. Non-penal measures such as community education, simplification of mining permits, economic empowerment programs, and local participation are crucial to addressing the socio-economic roots of illegal mining. Limitations: This study is confined to examining legal developments by comparing the Corruption Eradication Law with the provisions in the New Criminal Code. Contribution: This study contributes to the discourse on criminal law policy by highlighting the need for a balanced combination of penal and non-penal strategies to protect natural resources and achieve sustainable development. The findings can serve as a reference for local governments, law enforcement agencies, and policymakers in formulating more effective measures to eradicate illegal mining in Tulang Bawang and similar regions in Indonesia.